TINJAUAN YURIDIS SOSIOLOGIS TINDAK PIDANA KORUPSI YANG DILAKUKAN OLEH PEGAWAI NEGERI - , Rendy Indro Nursasongko, SH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to know and understand how to eradicate corruption by the government againstthe Public Servant who committed the crime of corruption. As we all know, the criminal acts of corruption is a crime that is extraordinary (extra-ordinary Crimes) that is not enough just to be handled by ordinary means, but must in ways extraordinary. The Indonesian government has taken various efforts to combat corruption through the establishment of Laws trom the Military Authorities Regulation Number: Prt/PM-06/1957 April 9, 1957 to Act No. 31 of 1999 amended by Law No. 20 Year 2001 on Eradication of corruption, followed by the Republic of IndonesiaPresidential Instruction NO.5 of2004 on the Acceleration of corruption. From this research can be known corruption in the civil servants continue to occur because of income / salary of Servants who lack their daily lives and their families fairly, forcing Servant seek additional income by doing criminal acts of corruption in order to provide for his life. Sociologically the values of living in a society strongly supports the occurrence of corruption trom birth until entry into the Civil Servants even when it became the main tasks and functions to hold the controlling government policy and are strongly associated with the bureaucracy that can take advantage of opportunities, power and opportunity they have to do this corruption makes the culture of corruption inherent in the society. Although the threat of Law Corruption is very heavy but the imposition of penalty for criminals are not so encouraging maximum Servants to continue to commit offenses Corruption to meet the needs of her family life and ensure his old life day after retiring trom Civil Service. Strategy, the Government in fighting corruption is a way of preventing the emergence of preventive of corruption directed at the things which become the cause of corruption so that it can be made pencegahanya crime and corruption could be minimized, in other words prevent corruption does not occur, the event detection acts of corruption then such act shall be known quickly and accurately, and acted upon as early as possible, repression is directed to each identified corruption can be checked and investigated promptly and accurately so that the real issue is known to sit for the later can be given appropriate sanctions by following the procedure law.